« Certains lieux de la peinture », comme expérience ontologique, de révélation chez María Zambrano - Camille Lacau St Guily (Cahiers de Civilisation Espagnole Contemporaine)
Through painting, as she testifies in several of her writings, among others in Algunos lugares de la pintura, through her autobiographical essay, Delirio y destino, or in her text entitled “El idiota” and in all her essays dedicated to Velázquez’s “Niño de Vallecas”, María Zambrano lives personal and “privileged” experiences, with the being. Painting offers her “revelations”. Some masterful works can put her in the presence of the soul of things and of any being, in the event of an encounter, which arises or can be woven in the duration, in a form of metanoïa of the heart and the intelligence, of the eyes and the ears, leading Zambrano to perceive the sublime in the non-being, in the damaged, the despised, the smallest, the simple, humble things, to be astonished in front of a face without apparent brilliance, that humanity rejects.